2021
DOI: 10.1007/s40368-021-00613-6
|View full text |Cite
|
Sign up to set email alerts
|

Children and parents perspectives on children’s dental treatment under general anesthesia: a narratology from Saskatoon, Canada

Abstract: Aim This study aimed to explore the emotional and psychological effects of dental treatment under general anesthesia (DTGA) on children and parents in Saskatoon city, Saskatchewan, Canada. Design Semi-structured interviews, video diaries, drawings, and a questionnaire were used to collect data. The study used a narrative perspective and thematic analysis to analyze data. Results The findings from children and their parents ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…There are numerous studies investigating parental and practitioner's perception of GA separately. Several studies showed that GA causes feelings of stress, fear and guilt in parents (AlQhtani and Pani, 2019, Amin et al, 2006, Baghdadi et al, 2021, Balmer et al, 2004. Gender aspects also have been discussed in decision making (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies investigating parental and practitioner's perception of GA separately. Several studies showed that GA causes feelings of stress, fear and guilt in parents (AlQhtani and Pani, 2019, Amin et al, 2006, Baghdadi et al, 2021, Balmer et al, 2004. Gender aspects also have been discussed in decision making (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cabe ressaltar que a incorporação dessas técnicas pelo profissional da odontologia é extremamente necessária, uma vez que ela busca tonar os tratamentos clínicos mais efetivos, evitando assim reincidências do problema, bem como auxilia na redução dos índices de erros de conduta e consequente dano ao paciente. Além disso, o manejo infantil ainda visa estabelecer uma comunicação com a criança, educar o paciente, construir uma relação de confiança, além de prevenir e aliviar o medo e a ansiedade (Baghdadi, Jbara & Muhajarine, 2021).…”
Section: Introductionunclassified